Regenerative Therapies for Articular Cartilage: Current Concepts, Clinical Outcomes, and Future Directions - Domińczak, Jan; Dobosz, Adam; Wojnowski, Antoni; Czarnecka, Sofia; Łuczyńska, Gabriela; Banatkiewicz, Joanna; Deka, Emilia; Bojanowska, Hanna; Babik, Karolina; Oliwia Bartkowska, (Journal of Education, Health and Sport, 2026)
Introduction and purpose. Articular cartilage injuries represent a significant clinical challenge due to the tissue’s limited intrinsic healing capacity, often progressing to osteoarthritis and chronic disability. Traditional treatments remain largely symptomatic, prompting extensive research into regenerative therapies aimed at restoring functional cartilage tissue. Description of the state of knowledge. We conducted a systematic analysis of recent literature (2020-2026) encompassing randomized controlled trials, systematic reviews, meta-analyses, and prospective cohort studies. Evidence was synthesized across multiple therapeutic modalities including mesenchymal stem cells (MSCs), autologous chondrocyte implantation (ACI/MACI), platelet-rich plasma (PRP), osteochondral transplantation, tissue engineering scaffolds, and emerging technologies such as 3D bioprinting, gene therapy, and exosome-based treatments. Matrix-associated autologous chondrocyte implantation (MACI) demonstrates significant long-term efficacy with large effect sizes (>0.8) in patient-reported outcomes at 2-15 years follow-up. Mesenchymal stem cells from various sources (bone marrow, adipose tissue, synovium, umbilical cord) show promise in clinical trials, with synovium-derived MSCs exhibiting particularly high chondrogenic potential. Comparative studies indicate that ACI/MACI and expanded MSC transplantation outperform microfracture for focal cartilage defects. Summary. Regenerative therapies have evolved significantly, with cell-based approaches demonstrating superior outcomes compared to traditional marrow stimulation techniques. However, challenges persist regarding optimal cell source, dosage, delivery methods, and long-term durability. Standardized protocols, large-scale randomized trials, and integration of emerging technologies are essential to advance the field toward personalized, effective cartilage regeneration strategies.